A STUDY ON CODE MIXING IN HITAM PUTIH TALK SHOW - ROFIQ, AUNUR (Jurnal Ilmiah Mahasiswa FIB, 2013)
In bilingualism, phenomenon of code mixing is something usual occurs in conversation. This phenomenon also occured in Hitam Putih talk show so the researcher is interested in conducting a study about code mixing in Hitam Putih talk show. There are two problems that need to be analyzed, they are: (1) What types of code mixing found in Hitam Putih talkshow episode Bola 28 December 2012, and (2) What are the reasons of using code mixing in Hitam Putih talkshow episode Bola 28 December 2012. This study uses a qualitative approach. The data of this study are only utterances which contain code mixing uttered by the presenter and guest stars of Hitam Putih talk show episode Bola 28 December 2012. The source of the data is collected from youtube.com. The results found are 71 data which consist of three types of code mixing: Intra-Sentential Code Mixing (51 data), Intra-Lexical Code Mixing (8 data), and Involving a Change of Pronunciation (12 data). The highest number is type of Intra-Sentential Code Mixing which is inserting English words or phrases into Indonesian sentences.   Keywords: Code Mixing, Hitam Putih, Utterance.